URGENSI SARANA DAN PRASARANA DALAM MENINGKATKAN KEBERHASILAN PENDIDIKAN AGAMA ISLAM DI SMP AL-LATHIFI GONDANGLEGI - Hosin, Zainal Muhammad; Hasyim, Muhammad (PAI RAFAH, 2024)
In improving the success of education in schools, several factors greatly influence it. One of the factors is educational facilities and infrastructure which is an important part of educational institutions. The success of Islamic Religious Education can be proven by superior student learning outcomes. The use of facilities and infrastructure is carried out concerning the teaching and learning process at school. The purpose of this study is (1) to know the condition of Islamic Religious education facilities and infrastructure at Al-Lathifi Gondanglegi Junior High School (2) to know how the management of facilities and infrastructure at Al-Lathifi Gondanglegi Junior High School (3) to know the Urgency of facilities and infrastructure in improving the success of Islamic Religious Education at Al-Lathifi Gondanglegi Junior High School. The method used in this research is a qualitative research method using a field research model. The research stage is in the form of research preparation, research implementation stage, data analysis stage, and final process. Data collection techniques were carried out by observation, and interviews with the principal, waka sarpras, and teachers at Al-Lathifi Gondanglegi Junior High School. The results of the study indicate that the condition of facilities and infrastructure at Al-Lathifi Gondanglegi Junior High School has not been said to be good because there are several facilities and infrastructure that are lacking and inadequate. The management of facilities and infrastructure has also not been carried out optimally due to difficulties in financing the procurement of facilities and infrastructure. So the urgency of facilities and infrastructure in improving the success of Islamic Religious education at Al-Lathifi Gondanglegi Junior High School is very important because it supports the process of learning. If sraana and prasrana are lacking then learning is less than optimal.